Pengaruh Minat Belajar Dan Pengalaman Belajar Terhadap Keterampilan Metakognitif Peserta Didik Madrasah Aliyah Dalam Pembelajaran Matematika - Aufa Silmi, Fara; Lestari, Mulyaningrum (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2024)
This study was undermined by a mathematical learning process that focused on the results resulting in a decrease in student interest and less varied learning experience, which had an impact on the metacognitive skills of the student. The study aims to identify the influence of learning interest and learning experience on student's metacognitive skills. This research uses field studies with a quantitative approach. So it can be concluded that: 1) interest in learning has a strong relationship ( 0,901) and has a positive and significant influence on metacognitive skills of 81.2%; 2) learning experiences have a strong link ( 0,869) and have a positive, significant impact on meta-cognitive skills of 75.5%; 3) learning interests and learning experiences are strongly linked ( 0,915) and have an active and significant effect on meta - cognitive abilities of 83.8% both partially and simultaneously.